Historia y actualidad de la Feria Franca de Montecarlo, Misiones mediante el entramado institucional - Bischoff, Rubén Darío; Bischoff, Doris Irene; Scherf, Abel Nicolás; Haussecker, Ricardo Daniel; Lamas, Veronica (Asociación Argentina de Horticultura, 2024)
Poster